👤

Calculati :

a) [tex][2x+[2x+( \frac{2x-1}{x-1} ) ^{-1} ]^{-1}]^{-1}[/tex] , pentru x=[tex] -\frac{1}{2} [/tex]

b) [tex] \frac{ \frac{1}{3}- x^{-2} }{9- (\frac{1}{x}) ^{-2}}: [ \frac{1}{ 3^{-2} (3+x)}-3* x^{-1}-8 ] [/tex] , pentru x=[tex] -\frac{1}{3} [/tex]


Răspuns :

a) se inlocuieste x cu -[tex] \frac{1}{2} [/tex] ; si rezulta :
[tex][ - \frac{2}{2} + [- \frac{2}{2} + ( \frac{- \frac{2}{2}-1}{- \frac{1}{2}-1}})^{-1} ]^{-1}]^{-1} [/tex] 



[tex] [ - 1 + [- 1 + ( \frac{- 1-1}{- \frac{3}{2})^{-1} ]^{-1}]^{-1} = [ - 1 + [- 1 + ( \frac{-4}{3})^{-1} ]^{-1} ]^{-1} [/tex]



[tex][ - 1 + (- 1 + \frac{3}{4} )^{-1}]^{-1} = ( - 1 + \frac{-1}{4} )^{-1} = ( \frac{-4}{4} + \frac{-1}{4} )^{-1} = ( \frac{-5}{4})^{-1} = - \frac{4}{5}[/tex]